THE EFFECT OF FERMENTATION TIME TO SNAKEHEAD FISH (Channa striata) BEKASAM QUALITY - Suyatno '; N. Ira Sari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe purpose of this research was to determine the effect of fermentationtime to snakehead fish (Channa striata) bekasam quality which was added roastedrice flour and pyloric caeca as a medium fermentation. The fish weighing 800-1000/fish was eviscerated, washed and salted with 30% of salt concentration for48 hours, then was added with 50% of roasted rice flour from fish weight. Themixture was grouped into 3 groups and divided 500g for each group. The eachtreatment was fermented for third day (H3), fifth day (H5) and seventh day (H7).Bekasam quality was evaluated for moisture content, protein content, NPNcontent, pH and lactic acid bacteria count. The results showed that snakehead fish(Channa striata) bekasam quality in seventh day (H7) fermentation was the besttreatment with appearance 5.8%, aroma 5.82%, taste 5.8%, moisture content63.28%, protein content 10.6%, NPN content 8.61%, pH 5.1 and a total lacticacid bacteria 182.3 x 103 cells / gram.Keywords : Channa striata, bekasam, roasted rice, phyloric caeca